Gonadotropin- releasing hormone agonist affects rat ovarian follicle development by interfering with FSH and growth factors on the prevention of apoptosis - Parborell, Maria Fernanda Agustina (2001)
Apoptosis is the biological process by which follicular cells are eliminated in atretic follicles. The aim of the present study was to examine the in vitro effect of a GnRH-a (leuprolide acetate, LA) and its interactions with FSH, dibutyryl cAMP, and growth factors (IGF-I, EGF, and FGF) on follicular apoptosis in early antral ovarian follicles obtained from prepubertal DES- treated rats. Follicles cultured 24 hr in the absence of hormones showed spontaneous onset of apoptotic DNA fragmentation. The presence of FSH suppressed the spontaneous onset of apoptotic DNA fragmentation (75-85%). Quantitative estimation of DNA cleavage from ovarian follicles revealed no significant changes in DNA fragmentation after in vitro LA treatment (1-100 ng/ml). However, coincubation with LA interfered partially with the effects of FSH on apoptosis suppression. This apoptosis suppression was also obtained by treatment with dibutyryl cAMP (80%), and was partially prevented by the presence of LA in the cultures. Follicles were cultured 24 hr with FGF, EGF, or IGF-I, and these factors suppressed DNA fragmentation (70, 60, and 70% respectively), while the presence of LA (100 ng/ml) in the culture medium prevented this effect. In conclusion, we show that the rescue from apoptotic DNA fragmentation produced in early antral follicles by FSH, cAMP, and growth factors, is prevented by coincubation with LA. This GnRH analog would thus interfere in the pathway of FSH, cAMP and/or growth factors by an as yet unknown mechanism.